Planning for the Cyclable City: The Gross Potential for Cycling - Marques, J.S. (12th CITTA International Conference on Planning Research, 2019)
In recent years, cycling has entered the urban mobility agenda in many regions worldwide, pushed by global commitments towards the transition to post-carbon societies. Whereas the state-of-the-art and state-of-practice is rather developed in matured cycling contexts, ‘starter cycling cities’ seem to be in a particularly disadvantaged situation, having no cycling tradition nor technical know-how, with little research focused on their specific problems and strategies. That is the case of Portuguese cities, all starters, which now face the targets raised by the recently-launched National Strategy for Active Mobility, aiming to increase the bicycle modal share in cities from the current average of 0.5% to 10% by 2030. Within this context, project ‘BooST – Boosting Starter Cycling Cities’ is developing a Starter City Roadmap, comprising a set of tools to support local authorities and urban planners in bringing about change. This presentation will focus on the assessment framework of the Gross Potential for Cycling (GPC), which identifies the city areas with higher and lower potential for cycling, given their built environment, land use and geographic characteristics. Considering the specificity of starter cycling cities, this tool looks at the gross potential, rather than the level of existing cycling infrastructure. By assessing the areas with higher potential, the tool supports starter cycling cities in deciding where to begin cycling investments, allowing targeted and customised policies for areas with differing potential within the same city, as well as a progressive strategy towards an integrated, inclusive, city-wide cycling network.